Development of Renal Failure without Proteinuria in a Patient with Monoclonal Gammopathy of Undetermined Significance: An Unusual Presentation of AL Kappa Amyloidosis - Yijuan Sun; Amarpreet Sandhu; Darlene Gabaldon; Jonathan Danaraj; Karen S. Servilla; Antonios H. Tzamaloukas (Case Reports in Nephrology)
AL amyloidosis complicating monoclonal gammopathy of undetermined significance (MGUS) has usually a predominant glomerular deposition of lambda light chain. Heavy proteinuria is one of its cardinal manifestations. A 78-year-old man with a 9-year history of IgG kappa light-chain-MGUS and normal urine protein excretion developed severe renal failure. Serum levels of kappa light chain and serum IgG had been stable while proteinuria was absent throughout the nine-year period. For the first eight years, he had stable stage III chronic kidney disease attributed to bladder outlet obstruction secondary to prostatic malignancy. In the last year, he developed progressive serum creatinine elevation, without any increase in the serum or urine levels of paraproteins or any sign of malignancy. Renal ultrasound and furosemide renogram showed no evidence of urinary obstruction. Renal biopsy revealed AL amyloidosis, with reactivity exclusive for kappa light chains, affecting predominantly the vessels and the interstitium. Glomerular involvement was minimal. Melphalan and prednisone were initiated. However, renal function continues deteriorating. Deposition of AL kappa amyloidosis developing during the course of MGUS predominantly in the wall of the renal vessels and the renal interstitium, while the involvement of the glomeruli is minimal, leads to progressive renal failure and absence of proteinuria. Renal biopsy is required to detect both the presence and the sites of deposition of renal AL kappa light chain amyloidosis.